2019
DOI: 10.1177/0301006619872062
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Space Perception in the Blind: Horizontal Sound Localization in Acoustically Simple and Complex Situations

Abstract: Even though it is widely believed that cross-modal neuroplasticity in blindness results in enhanced auditory spatial abilities, a growing number of studies also indicate disadvantages of blind persons for specific, more demanding audiospatial tasks. Here, the effects of blindness on horizontal sound localization were compared for simple localization of target sounds presented in isolation and target localization in an acoustically complex (cocktail-party) situation with multiple distractor sounds. While perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 118 publications
(216 reference statements)
1
6
0
Order By: Relevance
“…Inspired by animal studies, which demonstrated similar (though more long-term) plasticity of auditory and visual neural representations ( Knudsen and Knudsen, 1985 , 1989 ; Brainard and Knudsen, 1993 ; Knudsen, 1999 ; Hyde and Knudsen, 2000 , 2002 ; Zheng and Knudsen, 2001 ), experiments on this phenomenon led to the conception that vision calibrates human auditory spatial perception ( Recanzone, 1998 ; Lewald, 2002b ). Results obtained in blind and blindfolded sighted humans as well as in patients with visual-field loss demonstrating specific alterations of sound localization were in accordance with this view (e.g., Zwiers et al, 2001a , b ; Lewald, 2002a , c , 2013 ; Lewald et al, 2009a , b , 2013 ; Feierabend et al, 2019 ).…”
Section: Introductionsupporting
confidence: 82%
“…Inspired by animal studies, which demonstrated similar (though more long-term) plasticity of auditory and visual neural representations ( Knudsen and Knudsen, 1985 , 1989 ; Brainard and Knudsen, 1993 ; Knudsen, 1999 ; Hyde and Knudsen, 2000 , 2002 ; Zheng and Knudsen, 2001 ), experiments on this phenomenon led to the conception that vision calibrates human auditory spatial perception ( Recanzone, 1998 ; Lewald, 2002b ). Results obtained in blind and blindfolded sighted humans as well as in patients with visual-field loss demonstrating specific alterations of sound localization were in accordance with this view (e.g., Zwiers et al, 2001a , b ; Lewald, 2002a , c , 2013 ; Lewald et al, 2009a , b , 2013 ; Feierabend et al, 2019 ).…”
Section: Introductionsupporting
confidence: 82%
“…Feierabend et al (2019) reported that blind participants (a mixture of early and late onset) performed more poorly than sighted participants when localizing sounds at azimuths between −45° and +45°. This is the only study that we are aware of showing an effect in this direction for judgments of azimuth.…”
Section: Auditory Spatial Abilities That Are Enhanced As a Results Of...mentioning
confidence: 99%
“…Similarities in group performance have been attributed to ceiling effects due to the relatively low task difficulty when localizing single sounds from a limited number of possible source locations (Leclerc, et al, 2000). Feierabend, Karnath, and Lewald (2019) reported that blind participants (a mixture of early and late onset) performed more poorly than sighted participants when localizing sounds at azimuths between -45° and +45°. This is the only study that we are aware of showing an effect in this direction for judgments of azimuth.…”
Section: Sound Localization In Azimuthmentioning
confidence: 93%
“…Inspired by animal studies, which demonstrated similar (though more long-term) plasticity of auditory and visual neural representations (Knudsen & Knudsen, 1985, 1989Brainard & Knudsen, 1993;Knudsen, 1999;Hyde & Knudsen, 2000Zheng & Knudsen, 2001), experiments on this phenomenon led to the conception that vision calibrates human auditory spatial perception (Recanzone, 1998;Lewald, 2002b). Results obtained in blind and blindfolded sighted humans as well as in patients with visual-field loss demonstrating specific alterations of sound localization were in accordance with this view (e.g., Zwiers et al, 2001a, b;Lewald, 2002aLewald et al, 2009aLewald et al, , b, 2013Feierabend et al, 2019).…”
Section: Introductionmentioning
confidence: 67%